Nutrition during pregnancy and lactation: New evidence for the vertical transmission of extra virgin olive oil phenolic compounds in rats. (15th October 2022) - López-Yerena, Anallely; Grases-Pintó, Blanca; Zhan-Dai, Sonia; Pérez-Cano, Francisco J.; Lamuela-Raventos, Rosa M.; Rodríguez-Lagunas, Maria J.; Vallverdú-Queralt, Anna
Graphical abstract: Highlights: Phenolic compound metabolites profiles were determined in plasma and lactic serum. Total of 20 metabolites were identified, most of them were significantly increased with EVOO intake. Some expected phenolic compounds metabolites were detected in lactic serum. EVOO intake might positively affect the maternal breast milk. Abstract: Maternal breast milk provides the newborn with passive immunity and stimulates the maturation of the infant immune system. The aim of the present study was to evaluate the vertical transmission of phenolic compounds and their metabolites to offspring in rats fed with extra virgin olive oil (EVOO) during pregnancy and lactation. For this purpose, plasma and lactic serum from dams and plasma from offspring were analyzed by LC-ESI-LTQ-Orbitrap-MS. Both enzymatic and microbial metabolites of hydroxytyrosol and tyrosol were detected in dam plasma and lactic serum. In addition, significant levels of phenolic compounds and their metabolites were found in offspring plasma. The concentration and number of hydroxytyrosol derivatives was higher than those of tyrosol and the microbial metabolites were found in the highest concentration. The observed vertical transmission of EVOO phenolic compounds, whose health benefits are widely reported, provides further support for the importance of the maternal diet during pregnancy and lactation.